2017
DOI: 10.1002/2017gl074342
|View full text |Cite
|
Sign up to set email alerts
|

On the persistence and coherence of subpolar sea surface temperature and salinity anomalies associated with the Atlantic multidecadal variability

Abstract: This study identifies key features associated with the Atlantic multidecadal variability (AMV) in both observations and a fully coupled climate model, e.g., decadal persistence of monthly mean subpolar North Atlantic (NA) sea surface temperature (SST) and salinity (SSS) anomalies, and high coherence at low frequency among subpolar NA SST/SSS, upper ocean heat/salt content, and the Atlantic Meridional Overturning Circulation (AMOC) fingerprint. These key AMV features, which can be used to distinguish the AMV me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
125
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(148 citation statements)
references
References 58 publications
22
125
1
Order By: Relevance
“…The observed monopolar AMV SST pattern with high spatial coherence over the entire North Atlantic can be simulated in CGCMs showing a relatively strong linkage/correlation between the AMOC and AMV, whereas in slab ocean models the SST anomalies associated with AMV over the midlatitude western North Atlantic have an opposite sign with those over other regions of the North Atlantic (Sun et al, ). This red noise forcing mechanism is incompatible with high coherence among observed subpolar North Atlantic SST, SSS, upper ocean heat and salt content at multidecadal (but not at interannual) timescales, and decadal persistence of observed subpolar North Atlantic SST and SSS variations and much higher multidecadal power (above a red noise level) in their spectra (Zhang, ). Hence, the red noise mechanism as found in slab ocean models implies no decadal predictability other than the simple short persistence, and the most predictable component of the North Atlantic SST persists much longer with much higher predictability in CGCMs than in slab ocean models (Figures e–g), due to the important role of ocean dynamics in CGCMs (Yan et al, ).…”
Section: Amoc‐amv Linkagementioning
confidence: 99%
“…The observed monopolar AMV SST pattern with high spatial coherence over the entire North Atlantic can be simulated in CGCMs showing a relatively strong linkage/correlation between the AMOC and AMV, whereas in slab ocean models the SST anomalies associated with AMV over the midlatitude western North Atlantic have an opposite sign with those over other regions of the North Atlantic (Sun et al, ). This red noise forcing mechanism is incompatible with high coherence among observed subpolar North Atlantic SST, SSS, upper ocean heat and salt content at multidecadal (but not at interannual) timescales, and decadal persistence of observed subpolar North Atlantic SST and SSS variations and much higher multidecadal power (above a red noise level) in their spectra (Zhang, ). Hence, the red noise mechanism as found in slab ocean models implies no decadal predictability other than the simple short persistence, and the most predictable component of the North Atlantic SST persists much longer with much higher predictability in CGCMs than in slab ocean models (Figures e–g), due to the important role of ocean dynamics in CGCMs (Yan et al, ).…”
Section: Amoc‐amv Linkagementioning
confidence: 99%
“…The conceptual model for ocean mixed layer temperature can be used to discuss and evaluate the relative roles of the atmosphere and ocean (Barsugli & Battisti, ; Frankignoul, ; Frankignoul et al, ; Goodman & Marshall, ; Zhang, ): ρcphT∂t=Qnet+QO=qAλAT+qOλOT. …”
Section: Introductionmentioning
confidence: 99%
“…Zhang () later showed that inferences on the relative roles of qA and qO can be made from the false{QO,Tfalse} or false{Qnet,Tfalse} correlation, if the relative magnitudes of λ O and λ A are known. Given that λ O ≈ λ A over the midlatitude oceans, the correlation false{QO,Tfalse} can only be positive if qOqA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a wealth of literature that argues that coupled airsea interaction that fundamentally involves ocean dynamics is an important component of decadal variability, which is potentially predictable by coupled GCMs (Hayashi & Jin, 2017;McCarthy et al, 2015;Zhang, 2017). There is a wealth of literature that argues that coupled airsea interaction that fundamentally involves ocean dynamics is an important component of decadal variability, which is potentially predictable by coupled GCMs (Hayashi & Jin, 2017;McCarthy et al, 2015;Zhang, 2017).…”
Section: Subsurface Predictability In the North Atlanticmentioning
confidence: 99%